2017 IEEE International Symposium on Multimedia (ISM) 2017
DOI: 10.1109/ism.2017.95
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Analysis of Group-Specific Music Genre Taste from Collaborative Tags

Abstract: Abstract-In this paper, we describe the LFM-1b User Genre Profile dataset. It provides detailed information on musical genre preferences for more than 120,000 listeners and links to the LFM-1b dataset. We created the dataset by exploiting social tags, indexing them using two genre term sets, and aggregating the resulting annotated listening events on the user level. We foresee several applications of the dataset in music retrieval and recommendation tasks, among others to build and evaluate decent user models,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 10 publications
(9 reference statements)
4
16
0
Order By: Relevance
“…To exemplify also negative outliers, Table 8 shows for the United States, the first (highest global position) positive and negative outliers that appear along the trend when using the AF measure. Among the negative outliers, we find mostly hard rock and metal bands, which corroborates previous findings that these genres are underrepresented in the United States compared to the global mean [42].…”
Section: Analysis Of Global Versus Country-specific Mainstreamsupporting
confidence: 90%
“…To exemplify also negative outliers, Table 8 shows for the United States, the first (highest global position) positive and negative outliers that appear along the trend when using the AF measure. Among the negative outliers, we find mostly hard rock and metal bands, which corroborates previous findings that these genres are underrepresented in the United States compared to the global mean [42].…”
Section: Analysis Of Global Versus Country-specific Mainstreamsupporting
confidence: 90%
“…Our sample focused only on participants situated in the United States. Recent work showed that there are cultural differences in music consumption (e.g., [27,37,82,83,90]). Hence, cultural differences may also play a role in taxonomy usage and category preferences.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…The LFM-1b dataset may not necessarily generalize to the population at large. For instance, the usage of Last.fm data introduces a community bias [82]. In terms of age distribution, it may also not be representative to the global population at large [83].…”
Section: Datasetmentioning
confidence: 99%